Efek Sumber Karbon Berbeda terhadap Produksi â-Glukan oleh Saccharomyces Cerevisiae pada Fermentor Air Lift - Kusmiati, Kusmiati; Thontowi, Ahmad; Nuswantara, Sukma (Jurnal Natur Indonesia, 2011)
The need of â-glucan is increasing in food, medicine and cosmetic industry, because it becomes anticancer,antitumor and antiaging, increases immunosystem, and decreases cholesterol content in blood. The cell walls ofS. cerevisiae contain 80-90% polysaccharides that posses â-glucan. This research was aimed to obtain appropriatecarbon sources to increase the production of â-glucan. The carbon sources used were glucose, glucose commercial,sucrose and molases. The fermentation process was done by using air lift fermentor. The steps of fermentatonincluded regeneration of S. cerevisiae strain, preculture, fermentor preparation and running fermentor for 84hours. Sampling of S. cerevisiae culture was determined the cell growth by optical density (OD) usingspectrophotometer UV/VIS at ë 550 nm. The protein content was determined by Lowry method at ë 755 nm and thetotal glucose was measured by phenol sulphate method at ë 490 nm. The measurement result of cell growthshowed that the high intensity of S. cerevisiae in medium contain molases, but it did not show significant effectwhen compare to other carbon sources. The protein and carbohydrate contain in medium tended to decrease. Theresult of â-glucan on glucose, sucrose, glucose commercial and molases were 933,3, 1100, 1000, and966,7 mg/l. It can be concluded that sucrose and glucose commercial can replace the glucose to produce of â-glucan, because they are cheaper and easier to get. Beside that, molases can be used as an alternative carbonsource because it can produce of â-glucan as well as glucose.